MicroRNAs: a new tool in the complex biology of KRAS mutated non-small cell lung cancer? - Renaud, Stéphane; Seitlinger, Joseph; Massard, Gilbert (Journal of Thoracic Disease, 2017)
Despite several advances in the last decades in both medical and surgical management, with a 5-year overall survival (OS) not exceeding 15%, non-small cell lung cancer (NSCLC) remains the leading cause of cancer-related deaths worldwide (1). The past few years have seen an increased understanding in the molecular alterations of several cancers, helping clinicians to guide medical treatment and offer more accurate prognosis to patients. NSCLC was not left behind (2). Indeed, the recent discovery of oncogenic drivers such as activating mutations in the tyrosine kinase domain of the Epidermal Growth Factor Receptor (EGFR) has led to a dramatic increase in survival of patients harboring these mutations (3). Meanwhile, the prognostic and predictive values of EGFR mutations seem to be largely established in metastatic NSCLC (4), only a fleeting glimpse of clinical implications of many other mutations has been offered so far by the published literature, and might need further researches. One of the most promising molecular markers seems to rely in the mutations of the V-Ki-ras2 Kirsten rat sarcoma viral oncogene homolog (KRAS) gene. KRAS encodes for RAS proteins which are small GTPases bounding between inactive guanosine diphosphate (GDP) and active guanosine triphosphate (GTP) forms. RAS proteins are central mediators downstream of growth factor receptor signaling and therefore are critical for cell proliferation, survival, and differentiation. Approximately 15% to 25% of NSCLC adenocarcinomas exhibit KRAS mutations (5). In the very large majority of the cases, these mutations are missense mutations introducing an amino-acid substitution at codon 12, 13 or 61 of the exon 2 of the gene (6). This confers a constitutive activation of KRAS signaling pathways, including the PI3K-AKT-mTOR pathway, involved in cell survival, and the RAS-RAF-MEK-ERK pathway, involved in cell proliferation. The complexity of KRAS mutations is reflected by the difficulty to develop effective therapies for patients with NSCLC harboring such mutations, and so far KRAS mutations are related to a poor prognosis in both locally and advanced NSCLC patients (7,8).